THE IMPORTANCE OF SELF-CONTROL OF ARTERIAL PRESSURE IN INCREASE OF ADHERENCE OF PATIENTS TO TREATMENT OF ARTERIAL PRESSURE - Agaev, A.A.; Babaeva, A.D.; Гамзаєв М. А. (World of Medicine and Biology, 2012)
Observed 374 patients with supervised arterial hypertension (АH), from them 179 men and 195 women. An estimation of adherence of patients to treatment have spent questioning. Attached to treatment the patients who have typed 4 points, not attached - less than 4 points were considered. By the end of work self-control of arterial pressure (AP) carried out 268 of 374 observable patients. Adherence increase to treatment АH is one of the basic measures in achievement of medical effect and preventive maintenance of complications of this disease. Especially the great value has realisation of self-control of arterial pressure.
Keywords: arterial hypertension; preventive maintenance of an arterial hypertension; self-control of arterial pressure